2019
DOI: 10.2196/14269
|View full text |Cite
|
Sign up to set email alerts
|

A New Mental Health Mobile App for Well-Being and Stress Reduction in Working Women: Randomized Controlled Trial

Abstract: BackgroundAlthough the availability and use of mobile mental health apps has grown exponentially in recent years, little data are available regarding their efficacy.ObjectiveThis study aimed to evaluate the effectiveness of an app developed to promote stress management and well-being among working women compared with a control app.MethodsFemale employees at a private hospital were invited to participate in the study via mailing lists and intranet ads. A total of 653 individuals self-enrolled through the websit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 70 publications
(81 reference statements)
1
49
2
14
Order By: Relevance
“…Indeed, having similar experiences during the pandemic, peer health care workers may be in a unique position to provide practical and emotional support. A systematic review showed that digital peer support interventions led to improved self-coping and adaptation [27]. Through candid sharing of experiences and validation of feelings, app-based peer support, embedded in a social influence nudge strategy, could complement existing in-person support and have a positive impact on frontline workers' psychological well-being [52].…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, having similar experiences during the pandemic, peer health care workers may be in a unique position to provide practical and emotional support. A systematic review showed that digital peer support interventions led to improved self-coping and adaptation [27]. Through candid sharing of experiences and validation of feelings, app-based peer support, embedded in a social influence nudge strategy, could complement existing in-person support and have a positive impact on frontline workers' psychological well-being [52].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Individualized tailoring has been found to be an effective nudge in sustaining user engagement for digital mental health interventions [24][25][26]. In addition, provision of app-based resources yielded a positive outcome that alleviated chronic stress of working women [27]. Taken together, nudge theory has proved to be useful in effecting behavior change for mHealth interventions.…”
Section: Introductionmentioning
confidence: 98%
“…Although numerous studies have been conducted on MI apps [9,[14][15][16][17][18], few have used the algorithm of artificial neural networks (ANNs) in classifying MI, particularly with convolutional neural networks (CNNs). Traditionally, cutoff scores are often used in the classification of MI [19,20].…”
Section: App At Workplacementioning
confidence: 99%
“…Articles on MI apps have been published in the literature [14][15][16][17][18]43,44]. Over 45 articles were found by searching the keywords (app[title] and "mental health"[title]) in PubMed Central (PMC) on January 10, 2020.…”
Section: What This Knowledge Adds To What We Already Knowmentioning
confidence: 99%
“…It was evaluated for its efficacy at promoting stress management and well-being among working women. The results showed that the Flourish app was effective in reducing employees’ stress and at improving well-being [ 31 ].…”
Section: Introductionmentioning
confidence: 99%